2012
DOI: 10.1088/1742-6596/400/3/032070
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous electronic states of hollandite-type transition-metal oxides

Abstract: Abstract. We make the electronic structure calculations of transition-metal oxides with the hollandite-type crystal structure A2M8O16 using the generalized gradient approximation (GGA) in the density functional theory, where the Hubbard-type repulsive interaction is taken into account (GGA+U ). We first discuss generic electronic structures of the 3d (M =Ti, V, Cr, Mn) and 4d (M =Mo, Ru, Rh) series of the materials and then consider the origins of the metal-insulator transition observed in K2Cr8O16 and quasi-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…16 Additionally, the series of 4d transition-metal oxide hollandites, including B = Mo, Ru, and Rh, also displays interesting properties, including Q-1D conduction. 19 Most interestingly, BaRu 6 O 12 shows a highly unusual temperature dependence of magnetic susceptibility and has a possible quantum phase transition near T = 2 K between a metallic state and a competing, weakly localized state, tunable by the disorder and magnetic field. 20 In this work we report the structure of KIr 4 O 8 based on single-crystal X-ray diffraction (XRD) and report its physical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Additionally, the series of 4d transition-metal oxide hollandites, including B = Mo, Ru, and Rh, also displays interesting properties, including Q-1D conduction. 19 Most interestingly, BaRu 6 O 12 shows a highly unusual temperature dependence of magnetic susceptibility and has a possible quantum phase transition near T = 2 K between a metallic state and a competing, weakly localized state, tunable by the disorder and magnetic field. 20 In this work we report the structure of KIr 4 O 8 based on single-crystal X-ray diffraction (XRD) and report its physical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These compounds display various unusual physical properties, including metal–insulator transitions in KCr 4 O 8 , KV 4 O 8 , and Pb 1.6 V 8 O 16 ; spin-singlet formation in KV 4 O 8 ; ferromagnetism in KCr 4 O 8 ; and antiferromagnetism in Pb 1.6 V 8 O 16 . Additionally, the series of 4d transition-metal oxide hollandites, including B = Mo, Ru, and Rh, also displays interesting properties, including Q-1D conduction . Most interestingly, BaRu 6 O 12 shows a highly unusual temperature dependence of magnetic susceptibility and has a possible quantum phase transition near T = 2 K between a metallic state and a competing, weakly localized state, tunable by the disorder and magnetic field…”
Section: Introductionmentioning
confidence: 99%
“…19 More recently quasi one dimensional electron conduction has been suggested for KRu4O8 from Density Functional Theory (DFT) calculations. [20][21][22] These authors further suggested that KRu4O8 could be considered to be a Tomonaga-Luttinger liquid. 22,23 The influence of structural disorder in AxRu4O8 hollandite materials has been investigated, where A is K, Rb or a mixture of Na and Rb.…”
Section: Introductionmentioning
confidence: 97%
“…One-dimensional (1D) magnets have been extensively investigated during the last years as they could give an insight in the interplay between quantum and thermal fluctuations. In this respect, hollandite type materials are one of the 1D materials that have attracted a lot of interest [1][2][3]. These materials with a general chemical formula A x M 8 O 16 have a common tunnel structure constructed from the M 2 O 4 framework formed by the zigzag chains of edge-shared MO 6 octahedra and A cation at the tunnel sites, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%